Trends in cardiometabolic multimorbidity in non-elderly adult Medicaid enrollees, 2018–2022 - Chehal, Puneet Kaur; Lalwani, Pooja Dilip; Fuse Brown, Erin C.; Ali, Mohammed K.; Cunningham, Solveig A. (Frontiers in Epidemiology, 2025)
ImportanceMedicaid, as the largest U.S. insurer, can reduce cardiometabolic multimorbidity.ObjectiveAssess patterns and trends in cardiometabolic multimorbidity among Medicaid-enrolled adults.DesignAnalysis of 2018–2022 National Health Interview Survey data, a nationally representative cross-sectional survey.Conditions StudiedHypertension, hyperlipidemia, coronary heart disease, angina, heart attack, stroke, diabetes, and obesity.SettingU.S., 2018–2022.Participants11,090 adults (19–64 years) with Medicaid coverage.Main OutcomesProportion with one or multiple cardiometabolic conditions.Findings(a) 29.3% had one cardiometabolic condition; 29.7% had multimorbidity: 14.5% with 2, 8.0% with 3, and 7.1% with 4+ conditions. (b) Obesity, hypertension, and hyperlipidemia were the most common conditions either individually or together. (c) Obesity was more common in women than men, and women were more likely to have a single condition while men were more likely to have multimorbidity; these differences between men and women were larger in younger adults (<41 years) than older adults. (d) There was higher multimorbidity among older, non-working, and less educated Medicaid enrollees. (e) Prevalence of multimorbidity over time did not change but there was a decrease in the proportion of enrollees with no conditions which was offset by an increase in enrollees with a single condition. Conclusion29.7% of Medicaid-insured adults had cardiometabolic multimorbidity, and another 29.3% were at risk for it. Potential cuts to Medicaid coverage may exacerbate the burden of cardiometabolic multimorbidity in Medicaid enrollees.